Application of a combined supporting technology with U-shaped steel support and anchor-grouting to surrounding soft rock reinforcement in roadway - Wang, Hui; Zheng, Peng-qiang; Zhao, Wen-juan; Tian, Hong-ming (Journal of Central South University, 2018)
Soft rock surrounding deep roadway has poor stability and long-term rheological effect. More and larger deformation problems of surrounding rock occur due to adverse supporting measures for such roadways, which not only affects the engineering safety critically but also improves the maintenance costs. This paper takes the main rail roadway with severely deformation in China’s Zaoquan coal mine as an example to study the long-term deformation tendency and damage zone by means of in-situ deformation monitoring and acoustic wave testing technique. A three-dimensional finite element model reflecting the engineering geological condition and initial design scheme is established by ABAQUS. Then, on the basis of field monitoring deformation data, the surrounding rock geotechnical and rheological parameters of the roadway are obtained by back analysis. A combined supporting technology with U-shaped steel support and anchor-grouting is proposed for the surrounding soft rock. The numerical simulation of the combined supporting technology and in-situ deformation monitoring results show that the soft rock surrounding the roadway has been held effectively.